Emission balances of first -and second- generation biofuels: Case studies from Africa, Mexico and Indonesia - Frieden, D.; Pena, N.; Bird, D.N.; Schwaiger, H.; Canella, L. (Center for International Forestry Research, 2011)
This report examines and compares the greenhouse gas emissions of alternative first-generation and second-generation biofuel production pathways. The emissions balance analysed include greenhouse gas emissions from cultivation, land use change, processing and transport of biofuels. The biofuel production pathways reviewed are: -Biodiesel from palm oil in Indonesia, -Biodiesel from jatropha in South Africa and Mexico, -Bioethanol from sugar cane in South Africa, Mexico and Indonesia, -Bioethanol from wood in South Africa and Mexico, -Fischer-Tropsch diesel from wood in South Africa and Mexico Most calculations are undertaken using a tool developed by the BioGrace project funded by the European Union. For land use change emissions, three default values based on results from the partial equilibrium Global Biomass Optimisation Model (GLOBIOM) are used. An allocation of greenhouse gas emissions to the biofuel and its co-products is done by using the energy allocation method. The results show that wherever a land use change default value for non-wood feedstocks is used, this value dominates by far all other emission sources. Default land use change emissions for pathways using wood as feedstock are minor (short rotation coppice) or negative (wood from existing forests). However, woody feedstocks require second-generation conversion technologies. The least emission intensive first-generation pathways are bioethanol from sugar cane in Mexico and Indonesia due to the high productivity of sugar cane and the simple conversion process. Due to the limited country-specific database, a differentiation between countries or regions could not clearly be made. Differentiation can rather be done for the importance of particular factors such as feedstock productivity in conjunction with fertiliser use, allocation of co-products or the energy demand of specific conversion technologies.